Converting untreated waste office paper and chitosan into aerogel adsorbent for the removal of heavy metal ions. (1st August 2018) - Li, Zhanying; Shao, Lin; Ruan, Zehai; Hu, Wenbin; Lu, Lingbin; Chen, Yongjun
Highlights: Waste office paper was successfully converted to aerogel for Cu 2+ adsorption. Waste paper/chitosan aerogel (WP-CSA) possessed good mechanical strength. WP-CSA can always float on solution surface during the adsorption process. The adsorption mechanism of WP-CSA to Cu 2+ was demonstrated. Abstract: The utilization of waste paper, an obsolete recyclable resource, helps to save resources and protect environment. In this paper, an aerogel was prepared to convert the waste paper into a useful material, which was used to adsorb heavy metal ions and handle water pollution. Combining waste office paper and chitosan, the aerogel obtained the enhanced mechanical strength, acid resistance and high adsorption capacity (up to 156.3 mg/g for Cu 2+ ). This adsorption process obeyed the pseudo-second order model and the Langmuir model. The research showed that a coordination compound was formed between amino group and Cu 2+ during the adsorption process. The adsorbent could be regenerated well in 0.1 M H2 SO4 with up to 98.3% desorption efficiency. The low cost, environmental friendliness, excellent adsorption capacity and regeneration ability made this novel aerogel a promising adsorbent for heavy metal ions. And this conversion is an effective reuse way of waste paper too.